Hsc70-4 aggravates PolyQ-mediated neurodegeneration by modulating NF-κB mediated immune response in Drosophila - Rai, Saurabh; Tapadia, Madhu G. (Frontiers in Molecular Neuroscience, 2022)
Huntington’s disease occurs when the stretch of CAG repeats in exon 1 of the huntingtin (htt) gene crosses the permissible limit, causing the mutated protein (mHtt) to form insoluble aggregates or inclusion bodies. These aggregates are non-typically associated with various essential proteins in the cells, thus disrupting cellular homeostasis. The cells try to bring back normalcy by synthesizing evolutionary conserved cellular chaperones, and Hsp70 is one of the families of heat shock proteins that has a significant part in this, which comprises of heat-inducible and cognate forms. Here, we demonstrate that the heat shock cognate (Hsc70) isoform, Hsc70-4/HSPA8, has a distinct role in polyglutamate (PolyQ)-mediated pathogenicity, and its expression is enhanced in the polyQ conditions in Drosophila. Downregulation of hsc70-4 rescues PolyQ pathogenicity with a notable improvement in the ommatidia arrangement and near-normal restoration of optic neurons leading to improvement in phototaxis response. Reduced hsc70-4 also attenuates the augmented immune response by decreasing the expression of NF-κB and the antimicrobial peptides, along with that JNK overactivation is also restored. These lead to the rescue of the photoreceptor cells, indicating a decrease in the caspase activity, thus reverting the PolyQ pathogenicity. At the molecular level, we show the interaction between Hsc70-4, Polyglutamine aggregates, and NF-κB, which may be responsible for the dysregulation of signaling molecules in polyQ conditions. Thus, the present data provides a functional link between Hsc70-4 and NF-κB under polyQ conditions.